2021
DOI: 10.20473/ovz.v10i1.2021.18-24
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF RED DRAGON FRUIT SKIN EXTRACT (Hylocereus polyrhizus) ON THE NUMBER OF LEYDIG CELLS, DIAMETER OF SEMINIFEROUS TUBULES, AND TESTICULAR WEIGHT OF MALE MICE (Mus musculus) EXPOSURED WITH HOT TEMPERATURES

Abstract: This study aims to determine the effect of red dragon (Hylocereus polyrhizus) fruit peel extract (RDFPE) on the parameters of Leydig cells number, seminiferous tubules diameter, and testicular weight of mice (Mus musculus) exposed to heat (40°C). Twenty adult male mice were divided randomly into five groups. The control group (C) mice only received a placebo. Meanwhile, the treatment groups mice were exposed to heat for 45 minutes daily for 36 days and oral administration of placebo, RDFPE of 250, 500, and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Data obtained from the hematology analyzer test were then analyzed using the SPSS Version 20 (IBM Corp., NY, USA) and expressed in mean values and standard deviations [ 13 ] using the one-way ANOVA test [ 14 ]. If there is a difference between the treatments, it is continued with Ducan’s test with a significance level of 0.05 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data obtained from the hematology analyzer test were then analyzed using the SPSS Version 20 (IBM Corp., NY, USA) and expressed in mean values and standard deviations [ 13 ] using the one-way ANOVA test [ 14 ]. If there is a difference between the treatments, it is continued with Ducan’s test with a significance level of 0.05 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The number of Leydig cells in the testes was counted in five interstitial tissue fields in one preparation, and the averages were calculated. Observation was carried out using a microscope at 400x magnification with the assistance of image raster [17]. The diameter of seminiferous tubules was measured four times by drawing lines on the shortest and longest distances connecting the basement membrane of the seminiferous tubules in five fields of view in one preparation, and the average was calculated.…”
Section: Data Collectionmentioning
confidence: 99%
“…Disruption of testosterone synthesis by Leydig cells (Feng et al, 2005) had implications for the process of spermatogenesis and spermatozoa maturation in the epididymis which resulted in morphological abnormalities and decreased spermatozoa motility (Bashandy, 2007). A previous study reported that red dragon (Hylocereus polyrhizus) fruit peel extract restored the number of Leydig cell of mice (Mus musculus) that were exposed to heat (Prastyaningtyas et al, 2021). In addition, spermatozoa motility occurs due to the vibration of the spermatozoa tail.…”
Section: ¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯...mentioning
confidence: 99%